A method for predicting the heat resistance of high-purity oxygen-free copper strip for DBC ceramic copper cladding

By performing high-temperature heating and oxide film density detection on high-purity oxygen-free copper tape, combined with electrolytic polishing or nitric acid soaking treatment, the problem of difficult to quickly evaluate the heat resistance of copper tape in the prior art is solved, and rapid prediction and detection of ceramic covering requirements is achieved.

CN117740669BActive Publication Date: 2025-04-08CHINALCO LUOYANG COPPER PROCESSING CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311591414.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-27
Publication Date
2025-04-08
Estimated Expiration
2043-11-27

AI Technical Summary

Technical Problem

The prior art is difficult to quickly and easily evaluate the heat resistance performance of high-purity oxygen-free copper tapes and determine whether they can meet the grain size requirements after ceramic coating, which makes it difficult to detect.

Method used

By heating the high-purity oxygen-free copper tape at 900°C to 950°C for 30-60 minutes, the density of the oxide film on the surface is observed, and combined with electrolytic polishing or nitric acid soaking treatment, it is determined whether its heat resistance meets the requirements of ceramic coating.

Benefits of technology

It realizes rapid detection of the heat resistance of high-purity oxygen-free copper tape, can predict whether it can meet the grain size requirements after ceramic coating, simplifies the detection process, and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

A method for predicting the heat resistance of a high-purity oxygen-free copper strip for copper coating of DBC ceramics comprises the following steps: first, sampling and cleaning a high-purity oxygen-free copper strip with a Vickers hardness of ≥105, heating the strip at 900°C-950°C for 30-60 minutes in an air atmosphere after drying, and naturally cooling the strip to room temperature after being taken out of the furnace; then, judging the strip according to one of the following methods: (1) electropolishing the cooled sample, then taking the sample out to observe the shedding of an oxide film; if the oxide film on the surface of the sample is dense and difficult to remove and remains intact, it indicates that the heat resistance of the high-purity oxygen-free copper strip is good; (2) immersing the cooled sample in a nitric acid solution, taking the sample out after immersion to observe the shedding of an oxide film; if the oxide film on the surface of the sample is dense and difficult to remove and remains intact, it indicates that the heat resistance of the copper strip is good. The invention can realize rapid detection and evaluation of the heat resistance of the high-purity oxygen-free copper strip for copper coating of DBC ceramics, and judge whether the high-purity oxygen-free copper strip can meet the requirements for coating with ceramics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of nonferrous metal smelting and processing, and in particular relates to a method for predicting the heat resistance of a high-purity oxygen-free copper strip for DBC ceramic copper cladding. Background Art

[0002] As the core device for energy conversion and transmission, IGBT modules are widely used in new energy vehicles, rail transit, power engineering, and smart grids. Its high integration, high power, and miniaturization development trend require that the high-purity oxygen-free copper strips used for electronic packaging ceramic coatings must have high heat resistance, high thermal conductivity, low stress, and low thermal expansion.

[0003] The low thermal resistance DBC ceramic copper tape for IGBT modules is a laminated material made by directly bonding high-purity oxygen-free copper tape to a ceramic substrate on one side or both sides at a high temperature of 1060-1075°C. In order to facilitate the next step of etching, the copper tape is required to maintain a fine-grained state after lamination, with a grain size of ≤100μm, and a high requirement for the heat resistance of the copper tape grains.

[0004] How to quickly and easily evaluate the heat resistance of high-purity oxygen-free copper strips and determine whether they can meet the grain size requirements after ceramic cladding is difficult for current copper processing companies to test. First of all, the process details of ceramic cladding must be clear, and the same equipment must be configured to conduct effective testing. Seeking a method that can quickly detect the heat resistance of high-purity oxygen-free copper strips, which can quickly determine whether they can meet the requirements of ceramic cladding and be applied to industrial production, is an industry technical problem encountered by copper processing companies. Summary of the invention

[0005] The purpose of the present invention is to provide a method for predicting the heat resistance of high-purity oxygen-free copper strip for DBC ceramic copper cladding, so as to realize rapid detection and evaluation of the heat resistance of high-purity oxygen-free copper strip for DBC ceramic copper cladding, and judge whether the high-purity oxygen-free copper strip can meet the requirements of ceramic cladding.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is: a method for predicting the heat resistance of high-purity oxygen-free copper strip for DBC ceramic copper cladding, first, the high-purity oxygen-free copper strip with Vickers hardness ≥ 105 is sampled and cleaned, and after drying, it is heated at 900℃-950℃ in an air atmosphere for 30-60 minutes, and naturally cooled to room temperature after being taken out of the furnace; then, it is judged according to one of the following methods:

[0007] (1) The cooled sample is electropolished and then taken out to observe the oxide film shedding. If the oxide film on the surface of the sample is dense and difficult to remove and remains intact, it means that the heat resistance of the high-purity oxygen-free copper strip is good and can meet the requirements of DBC lamination of the high-purity oxygen-free copper strip and the ceramic substrate; otherwise, the heat resistance of the high-purity oxygen-free copper strip cannot meet the requirements of DBC lamination of the high-purity oxygen-free copper strip and the ceramic substrate;

[0008] (2) The cooled sample is immersed in a nitric acid solution, and then taken out to observe the oxide scale shedding. If the oxide film on the surface of the sample after immersion is dense and difficult to remove and remains intact, it means that the copper strip has good heat resistance and can meet the requirements of DBC lamination of high-purity oxygen-free copper strip and ceramic substrate; otherwise, the heat resistance of the high-purity oxygen-free copper strip cannot meet the requirements of DBC lamination of high-purity oxygen-free copper strip and ceramic substrate.

[0009] The electrolyte used in the electrolytic polishing treatment is prepared by mixing water and 85% phosphoric acid in a volume ratio of 3:4.

[0010] The working voltage in the electrolytic polishing process is 30-50V, and the processing time is 1-10 seconds.

[0011] The volume fraction of the nitric acid solution is 30-50%, and the soaking time is 5-20 minutes.

[0012] When cleaning the sample, a mixed solution of dilute sulfuric acid and dilute nitric acid is used as the cleaning solution.

[0013] The volume fractions of the dilute sulfuric acid and the dilute nitric acid are both 10%, and the volume ratio of the dilute sulfuric acid to the dilute nitric acid is 1:1.

[0014] The sample is heated using a high temperature resistance furnace.

[0015] The high temperature resistance furnace is a muffle furnace or a tubular resistance furnace.

[0016] The principle of the present invention is that the ceramic-clad high-purity oxygen-free copper strip of the DBC process usually requires the high-purity oxygen-free copper strip HV≥105. The inventors found that: in an air atmosphere, after the high-purity oxygen-free copper strip sample with HV≥105 is heated at 900~950℃ for 30~60 minutes, the density of the oxide film on the surface of the sample is closely related to the heat resistance of the high-purity oxygen-free copper strip at high temperature.

[0017] For oxygen-free copper strip with HV≥105, after heating at 950℃ for 30 minutes, the oxide scale and the matrix are easily separated, and the grain size of the strip after baking is usually above 500μm, and the heat resistance is poor; if the oxide scale and the matrix are tightly combined, the grain size of the strip after baking is ≤80μm, and after DBC ceramic cladding at a temperature of 1060-1075℃, the grain size of the copper strip is detected to be ≤100μm, and the heat resistance can meet the use requirements.

[0018] Therefore, by detecting and observing the density of the oxide film after baking, it is possible to predict whether the high-purity oxygen-free copper strip meets the heat resistance requirements of DBC ceramic coating, and the accuracy of the heat resistance prediction can be verified by the average grain size of the copper strip after high-purity oxygen-free copper strip is coated with the ceramic substrate DBC.

[0019] The beneficial effects of the present invention are as follows: the present invention solves the difficult problem of predicting the heat resistance of high-purity oxygen-free copper strip for DBC ceramic copper cladding before the copper strip leaves the factory. The operation process is mainly realized by Vickers hardness detection and oxide scale peeling resistance. By creatively conducting oxide scale peeling test and combining conventional inspection methods, the difficult problem of the detection method of the heat resistance of high-purity oxygen-free copper strip for DBC ceramic cladding is solved. The present invention is suitable for the production of high-purity oxygen-free copper strip and can quickly predict whether the heat resistance of the high-purity oxygen-free copper strip meets the requirements of DBC ceramic cladding. DETAILED DESCRIPTION

[0020] The present invention will be further described in detail below in conjunction with the embodiments, but they are not intended to limit the invention in any way.

[0021] A method for predicting the heat resistance of a high-purity oxygen-free copper strip for DBC ceramic copper cladding, wherein the high-purity oxygen-free copper refers to pure copper with a copper content of 99.99% and an oxygen content of less than 10 ppm, and the method comprises the following steps:

[0022] 1. Sampling: Cut two square samples of about 50×50mm with the thickness of finished product from the produced coiled strip;

[0023] 2. Vickers hardness test: Use a Vickers hardness tester to test the sample in accordance with the method of "Vickers hardness test for metal materials" in GB / T4340.1-2009;

[0024] 3. For samples with Vickers hardness of 105 or above, oxide film peeling test shall be carried out;

[0025] 3.1. Cleaning: Use a mixed solution of dilute sulfuric acid (10% volume fraction) and dilute nitric acid (10% volume fraction) in a volume ratio of 1:1, then rinse with running water and dry;

[0026] 3.2. Baking: Place the cleaned and dried sample on a stand in a high-temperature resistance furnace and heat it at 900℃-950℃ in air atmosphere for 30-60 minutes;

[0027] 3.3 Cooling: After being taken out of the furnace, cool naturally to room temperature and visually observe the peeling of the oxide film on the surface of the copper substrate;

[0028] 3.4. Electrolytic polishing: clamp the cooled sample in step 3.3 with a clamp and place it in an electrolyte, turn on the power supply, the working voltage is 30-50V, the processing time is 1-10 seconds, and after polishing, take it out to observe the shedding of the oxide film; the electrolyte is a mixture of water and 85% phosphoric acid in a volume ratio of 3:4.

[0029] 3.5. Nitric acid immersion: Soak the cooled sample in step 3.3 in a 30-50% nitric acid solution for 5-20 minutes. Take it out after immersion and observe the oxide scale shedding.

[0030] Judgment method: (1) For the sample treated with electrolytic polishing, if the oxide film on the surface of the sample is dense and difficult to remove after polishing, and remains intact, it means that the copper strip has good heat resistance and can meet the requirement that the average grain size of the copper strip is ≤100μm after the 1060-1075℃ copper strip is laminated with the ceramic substrate;

[0031] (2) For the samples treated with nitric acid immersion, the oxide film on the surface of the samples after immersion is dense, difficult to remove, and remains intact, which means that the copper strip has good heat resistance and can meet the requirement that the average grain size of the copper strip is ≤100μm after the 1060-1075℃ copper strip is laminated with the ceramic substrate.

[0032] Both steps 3.4 and 3.5 can be used to treat the oxide film of the copper strip. You only need to select one of the two steps and use the judgment method corresponding to the selected step to predict the heat resistance.

[0033] In the above method, the high temperature resistance furnace can be a muffle furnace or a tubular resistance furnace.

[0034] The following examples and comparative examples are provided to illustrate the detection method of the above invention in more detail, but the present invention is not limited thereto.

[0035] First, oxygen-free copper with the same composition content is processed to the same finished strip thickness to obtain strips with the same or different hardness.

[0036] Take samples of the same grade of strip, clean them and bake them in a high temperature resistance furnace at 900-950℃ for 30-60 minutes. After baking, take them out and cool them naturally to room temperature. Use the above methods (1) and (2) to test and visually observe the combination of the oxide film on the copper substrate surface and the copper strip surface and the removal of the black oxide film.

[0037] When using method (1) and method (2) for testing, electrolytic polishing or nitric acid immersion treatment is required accordingly.

[0038] The copper strip used in Examples 1 and 2 is C10100, and the heating condition is 950°C / 30 minutes; the copper strip used in Examples 3 and 4 is TU1, and the heating condition is 900°C / 60 minutes; the copper strip used in Examples 5 and 6 is C10200, and the heating condition is 920°C / 45 minutes. The copper strips used in Comparative Examples 1 and 2 and the heating conditions are the same as those in Example 1; the copper strips used in Comparative Examples 3 and 4 and the heating conditions are the same as those in Example 3; the copper strips used in Comparative Examples 5 and 6 and the heating conditions are the same as those in Example 5.

[0039] Hardness HV: The hardness of the test material is measured, and if the HV reaches 105 or above, it is evaluated as "qualified", and if the HV is lower than 105, it is evaluated as "unqualified". The specific test values ​​of HV of each embodiment and comparative example are listed in Table 1.

[0040] Oxide film peeling: The oxide film of the sample after heating, baking and natural cooling is subjected to the above-mentioned electrolytic polishing and acid leaching treatment, and the oxide film peeling is observed. If the oxide film is not easy to fall off, it is evaluated as "dense", otherwise it is evaluated as "not dense". The oxide film peeling conditions of each embodiment and comparative example are listed in Table 1.

[0041] Heat resistance verification: Heat resistance verification requires measuring the average grain size of the copper strip after sintering. When the average grain size is ≤100μm, it means that the heat resistance of the copper strip meets the requirements for lamination with the ceramic substrate.

[0042] The surface of the copper strip baked in the air of the present invention has an oxide film. If the average grain size of the copper strip is to be determined, the oxide film needs to be removed, but the removal of the oxide film is difficult. Therefore, in order to facilitate the heat resistance verification, each sample of the embodiment is DBC-laminated with a ceramic substrate under a vacuum environment, and the sintering temperature is 1070°C. After lamination, the average grain size of the copper strip after lamination is measured according to the standard "grain size of copper and copper alloys" method. If the average grain size is ≤100μm, it is evaluated as "qualified", indicating that the corresponding copper strip has good heat resistance and meets the requirements for lamination with a ceramic substrate; otherwise, it is evaluated as "unqualified", indicating that the thermal stability of the corresponding copper strip does not meet the requirements for lamination with a ceramic substrate.

[0043] For the comparative example, a copper strip of the same grade and thickness as the respective embodiments is selected, and the hardness of the copper strip of the comparative example is similar to that of the corresponding copper strip of the embodiments, but the copper strip of the comparative example and the corresponding embodiment are produced by different manufacturers, and the processes are not completely the same. The copper strip of the comparative example is treated by the method of the present invention, and is verified according to the above-mentioned heat resistance verification method, and the average grain size of the copper strip is determined. The detection values ​​of the average grain size of the respective embodiments and comparative examples are listed in Table 1.

[0044] Table 1 Test results of embodiments and comparative examples

[0045]

[0046] In Examples 1-6 shown in Table 1, high-purity oxygen-free copper strips of different grades and thicknesses for DBC ceramic lamination are treated by the method of the present invention. Visual inspection shows that the oxide scale of the samples is tightly bonded to the substrate and is not easily removed by electrolysis or acid leaching. It can be predicted that the copper strip has good heat resistance and can meet the lamination requirements with the ceramic substrate. After heat resistance verification, the copper strips of Examples 1-6 are laminated with the ceramic substrate under vacuum conditions, and the average grain size of the copper strips is less than 100 μm.

[0047] In Comparative Examples 1-6 shown in Table 1, the brand and thickness of the oxygen-free copper strip are the same as those of the embodiment, and the hardness value of the strip is also close to that of the embodiment 1-6. After the oxygen-free copper strip is treated by the method described in the present invention, the oxide film of the sample tested by visual inspection is not tightly bonded to the substrate, and some of them fall off after cooling. The unfallen parts can be removed by electrolysis or acid leaching to obtain a bright copper surface. In this case, it is predicted that the heat resistance of the copper strip is poor and cannot meet the requirements for lamination with the ceramic substrate. After further heat resistance verification, the copper strips of Comparative Examples 1-6 were laminated with the ceramic substrate under vacuum conditions, and the average grain size of the copper strips was greater than 100μm.

[0048] Through the comparison of the above embodiments and comparative examples and the corresponding heat resistance verification, it is found that the oxide film peeling test results correspond to the heat resistance verification results. Therefore, the method for predicting the heat resistance of the high-purity oxygen-free copper strip for DBC ceramic copper cladding described in the present invention is feasible.

[0049] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the same. Those skilled in the art should understand that the specific implementation modes of the present invention may be modified or replaced by equivalents with reference to the above embodiments. Any modifications or equivalent replacements that do not depart from the spirit and scope of the present invention are within the scope of protection of the pending claims.

Claims

1. A method for predicting the heat resistance of high-purity oxygen-free copper strip for DBC ceramic copper cladding, characterized in that: First, sample and clean the high-purity oxygen-free copper strip with Vickers hardness ≥ 105, dry it, heat it at 900℃-950℃ in air atmosphere for 30-60 minutes, and cool it naturally to room temperature after it comes out of the furnace; then, judge it according to one of the following methods: (1) The cooled sample is electropolished, and then taken out to observe the oxide film shedding. If the oxide film on the surface of the sample is dense and difficult to remove and remains intact, it means that the heat resistance of the high-purity oxygen-free copper strip is good and can meet the requirements of DBC lamination of the high-purity oxygen-free copper strip and the ceramic substrate; otherwise, the heat resistance of the high-purity oxygen-free copper strip cannot meet the requirements of DBC lamination of the high-purity oxygen-free copper strip and the ceramic substrate; The electrolyte used in the electrolytic polishing treatment is prepared by mixing water and 85% phosphoric acid in a volume ratio of 3:

4. The working voltage in the electrolytic polishing treatment is 30-50V, and the treatment time is 1-10 seconds. (2) The cooled sample is immersed in a nitric acid solution, and then taken out to observe the oxide scale shedding. If the oxide film on the surface of the sample after immersion is dense and difficult to remove and remains intact, it means that the copper strip has good heat resistance and can meet the requirements of DBC lamination of high-purity oxygen-free copper strip and ceramic substrate; otherwise, the heat resistance of the high-purity oxygen-free copper strip cannot meet the requirements of DBC lamination of high-purity oxygen-free copper strip and ceramic substrate; The volume fraction of the nitric acid solution is 30-50%, and the soaking time is 5-20 minutes.

2. The method for predicting the heat resistance of high-purity oxygen-free copper strip for DBC ceramic copper cladding according to claim 1, characterized in that: When cleaning the sample, a mixed solution of dilute sulfuric acid and dilute nitric acid is used as the cleaning solution.

3. The method for predicting the heat resistance of high-purity oxygen-free copper strip for DBC ceramic copper cladding according to claim 2, characterized in that: The volume fractions of the dilute sulfuric acid and the dilute nitric acid are both 10%, and the volume ratio of the dilute sulfuric acid to the dilute nitric acid is 1:

1.

4. The method for predicting the heat resistance of high-purity oxygen-free copper strip for DBC ceramic copper cladding according to claim 1, characterized in that: The sample is heated using a high temperature resistance furnace.

5. The method for predicting the heat resistance of high-purity oxygen-free copper strip for DBC ceramic copper cladding according to claim 4, characterized in that: The high temperature resistance furnace is a muffle furnace or a tubular resistance furnace.

Citation Information

Patent Citations

  • Method for pre-judging thermal stability of oxygen-free copper strip for AMB ceramic copper-clad plate

    CN117969318A